Reverse engineering and introduction to engineering design - Siegkas, Petros (My University, 2020)
This paper describes practical elements during two terms of a first-year module within which CDIO standards are implemented. The aim of this practical module is for students to practice their fundamental knowledge and develop the required skills to complete projects that are structured according to industry standards. Several skills are involved in working within a professional engineering environment, beyond the strictly technical knowledge. The intention is to make the students also aware of these skills. During the first term of year one, the module includes a team-based reverse engineering project. Students are assigned to teams and given an appliance. They are expected to conceptually and physically deconstruct the device and analyze the relevant aspects of both of its parts and as a whole. Aspects would include scientific principles related to function, design considerations, the context of use, etc. The teams will then propose improvements on individual parts and the device as a whole, in terms of either function, price, manufacturing, or sustainability. The work is presented to the class and compiled into a group report. During the second term, the students are trained in design software (Autodesk Fusion 360 CAD, CAE, CAM), including basic finite element simulation, and are given two design tasks. The first is to use laser cutting to design a small wooden bridge based on certain specifications (e.g., dimensions, load-bearing), including some aesthetic elements, using limited resources (i.e., material allowance). The second is to design and optimize (in terms of mass) a support structure of certain dimensions and load-bearing capacity. The structures are then manufactured and assembled, i.e., laser-cut, and 3D printed correspondingly, weighted and tested for their load-bearing capacity. Assessment is based on a relevant portfolio. Throughout the two terms, lectures are delivered on project management and product development, as well as case studies by guest lecturers of various engineering fields. The module has been very well received with high student ratings in relevant surveys.
Keywords: active learning; CAD/CAE/CAM; design process; Introduction to engineering; Standard 1, 3, 4, 5, 8, 11